Developing a Prophetic Education Programme to Prevent Violence in Early Childhood: A Study of PAUD Institutions in Indonesia - Juntika Nurihsan; Mubiar Agustin; Idat Muqodas; Rivaldo Juliansyah; Putri Andita Rahmaningtyas; Khairatul Ulya Ilma (STAI Hubbulwathan Duri, 2025)
Violence against children—including physical, emotional, verbal, sexual abuse, and neglect—has become a critical concern in Indonesia, including in Early Childhood Education (PAUD) settings where safety should be paramount. Alarmingly, some cases involve educators as perpetrators. This study addresses the urgent need for preventive interventions by developing a Prophetic Education programme grounded in ethical and spiritual values. This study employed a quasi-experimental design involving early childhood teachers from several Raudhatul Athfal (RA) institutions in Majalengka. An initial survey of 100 teachers was conducted to assess tendencies toward violent behavior. Based on these results, 30 teachers were selected and randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received structured training based on prophetic values such as compassion, patience, and empathy, while the control group followed conventional parenting activities. Data were analyzed using Wilcoxon and independent t-tests. The post-test findings showed significant differences between the experimental and control groups across all violence dimensions—physical, verbal, emotional, and behavioral determinants. Teachers in the experimental group demonstrated reduced tendencies toward violent behavior, and children under their supervision showed improved emotional regulation and interpersonal conduct. The study concludes that Prophetic Education is effective in reducing violence in early childhood settings. The programme offers a culturally grounded, values-based framework that can inform teacher training, early childhood curricula, and educational policy reforms aimed at fostering safe, respectful, and nurturing learning environments.